2018
DOI: 10.3390/ijms19082206
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Source Dependent Changes in Central Sugar Metabolism Maintain Cell Wall Assembly in Mitochondrial Complex I-Defective frostbite1 and Secondarily Affect Programmed Cell Death

Abstract: For optimal plant growth, carbon and nitrogen availability needs to be tightly coordinated. Mitochondrial perturbations related to a defect in complex I in the Arabidopsis thaliana frostbite1 (fro1) mutant, carrying a point mutation in the 8-kD Fe-S subunit of NDUFS4 protein, alter aspects of fundamental carbon metabolism, which is manifested as stunted growth. During nitrate nutrition, fro1 plants showed a dominant sugar flux toward nitrogen assimilation and energy production, whereas cellulose integration in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 123 publications
(179 reference statements)
0
6
0
Order By: Relevance
“…DJ-1 may also serve a similar function in plants because it has been shown that Arabidopsis insertional mutants possessing elevated DJ-1A levels are characterized by increased protection against environmental stress conditions achieved through DJ-1A-dependent activation of ROS-quenching enzymes, including superoxide dismutase 1 (SOD1) and glutathione peroxidase 2 (GPX2) (Xu et al 2010 ), or interaction with ascorbate peroxidase 1 (APX1) (Xu and Møller 2010 ). Arabidopsis DJ-1A is localized to the cytosol and the nucleus (Xu et al 2010 ) and its upregulated expression may be related to an increased demand for enhanced antioxidant capacity under ammonium feeding conditions when oxidative stress occurs (Podgórska et al 2018a , b ). Although DJ-1D displays the most distinct glyoxalase activity among all the DJ-1 proteins (Kwon et al 2013 ), neither upregulation of DJ-1D by ammonium (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…DJ-1 may also serve a similar function in plants because it has been shown that Arabidopsis insertional mutants possessing elevated DJ-1A levels are characterized by increased protection against environmental stress conditions achieved through DJ-1A-dependent activation of ROS-quenching enzymes, including superoxide dismutase 1 (SOD1) and glutathione peroxidase 2 (GPX2) (Xu et al 2010 ), or interaction with ascorbate peroxidase 1 (APX1) (Xu and Møller 2010 ). Arabidopsis DJ-1A is localized to the cytosol and the nucleus (Xu et al 2010 ) and its upregulated expression may be related to an increased demand for enhanced antioxidant capacity under ammonium feeding conditions when oxidative stress occurs (Podgórska et al 2018a , b ). Although DJ-1D displays the most distinct glyoxalase activity among all the DJ-1 proteins (Kwon et al 2013 ), neither upregulation of DJ-1D by ammonium (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…7 d) and were more resistant to exogenous d -lactate (K. Borysiuk, B. Szal, results not presented). Such a feature seems not to be a simple consequence of the differences in the level of electron acceptor for reaction by d -LDH since cytochrome c (cyt c ) levels are lower in ammonium-grown fro1 plants than in WT plants (Podgórska et al 2018a , b ). However, d -LDH function requires oxidized cyt c availability, and its level depends on the electron loading process and forwarding toward Complex IV of the mtETC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this Special Issue, “Plant Mitochondria”, a total of 19 articles were accepted with 15 original research articles and 4 review articles broadly covering the field of plant mitochondrial research (Table 1). Manuscripts focused on protein synthesis and degradation [3,4,5,6], abiotic stress [7,8,9,10], OxPhos [11,12,13,14], protein import [15,16,17], ROS and antioxidants [18], and CMS [19,20].…”
mentioning
confidence: 99%
“…Galega Vulgar (European olive). Podgórska et al [12] examined the Complex 1 mutant fro1 ( frostbite 1 ) that has a point mutation in the 8 kDa Fe-S subunit NDUFS4 grown on different nitrogen sources. When these plants were grown on NO 3 - they showed a carbon flux towards nitrogen assimilation and energy production, whereas cellulose integration into the cell wall was restricted.…”
mentioning
confidence: 99%